Effect of an ethanol cross-linker on universal adhesive. Issue 12 (December 2020) - Comba, Allegra; Maravić, Tatjana; Villalta, Virginia; Tozzola, Serena; Mazzitelli, Claudia; Checchi, Vittorio; Mancuso, Edoardo; Scotti, Nicola; Tay, Franklin R.; Breschi, Lorenzo; Mazzoni, Annalisa
Highlights: The possibility to use an ethanol-based cross-linker as a primer seems to be a promising option in terms of bond strength. N, N'-dicyclohexylcarbodiimide (DCC) pre-treatment efficiently preserves bond strength over time. Matrix-metalloproteinases activity seems to be influenced by the application mode of a universal adhesive. Abstract: Objective: To evaluate the effects of N, N'-dicyclohexylcarbodiimide (DCC), an ethanol-based dentin cross-linker, on the immediate and long-term microtensile bond strength (μTBS) and nanoleakage expression of a universal adhesive employed in self-etch mode (SE) or etch-and-rinse mode (ER). The effect of DCC on the dentinal MMP activity was also investigated by means of in-situ zymography. Methods: Eighty freshly extracted human molars were sectioned to expose mid-coronal dentin surfaces. The teeth were assigned to one of the following groups, according to the dentin surface priming/adhesive approach: (G1): DCC pre-treatment and Scotchbond Universal (SBU) in ER mode; (G2): SBU in ER mode; (G3): DCC pretreatment and SBU in SE mode; (G4): SBU in SE mode. μTBS test was performed immediately (T0 ) or after 1-year aging (T12 ) in artificial saliva. Ten additional teeth per group were prepared for nanoleakage evaluation (N = 5) and for in-situ zymography (N = 5). Results: Three-factor analysis of variance revealed significant difference for the variables DCC pretreatment, application mode and aging (p < 0.05) for both microtensile bond strength testing and in-situ zymography. Nanoleakage analysis revealed reduced marginal infiltration of DCC experimental groups both at T0 and T12 . Significance: The use of an ethanol-based primer containing DCC appears to be promising in preserving the stability of the adhesive interface of a universal adhesive, especially in the SE mode.